2020
DOI: 10.1159/000505059
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Proton Pump Inhibitor in Cirrhotics with Variceal Bleeding: A Systemic Review and Meta-Analysis

Abstract: Background and Aims: Proton pump inhibitor (PPI) was widely used in cirrhotic patients with variceal bleeding empirically rather than evidence-based practice. We aimed to evaluate the plausible indication of PPI use in variceal bleeding cirrhotic patients and figure out whether it can decrease the re-bleeding rate after endoscopic therapy. Furthermore, we also investigated the association between PPI and bleeding-related mortality in these patients. Methods: We have searched in PubMed, Medline, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
(59 reference statements)
2
17
0
Order By: Relevance
“…In our results, the use of PPIs was associated with a reduced risk of post-BL ulcer bleeding (odds ratio, 0.77; 95% CI: 0.603-0.983). This nding is in agreement with those of several other studies [13,19]. The use of PPIs to reduce the size of an ulcer and lower the risk of re ux oesophagitis and post-prophylactic BL bleeding has been established [12,20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our results, the use of PPIs was associated with a reduced risk of post-BL ulcer bleeding (odds ratio, 0.77; 95% CI: 0.603-0.983). This nding is in agreement with those of several other studies [13,19]. The use of PPIs to reduce the size of an ulcer and lower the risk of re ux oesophagitis and post-prophylactic BL bleeding has been established [12,20].…”
Section: Discussionsupporting
confidence: 91%
“…alcoholic liver disease, nonalcoholic fatty liver disease, viral, alcoholic liver disease plus viral, autoimmune liver disease or other), haemostasis treatment urgency (i.e. elective or emergent) and adjuvant use of PPIs [12,13]. The other categorical variables included high-risk stigmata (i.e.…”
Section: Outcomes and Variablesmentioning
confidence: 99%
“…EVB is the main influencing factor for the increased mortality in patients with liver cirrhosis ( 3 ). The mortality of the first bleeding was about 20–30% if an active intervention was not carried out ( 4 ). Within 2 years after the first bleeding, the rebleeding rate and mortality increased significantly, which threatened the safety of patients ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] About 46%-78% of the patients with cirrhosis have been treated with acid suppression therapy, as it may be associated with a reduction in gastrointestinal rebleeding in cirrhotic patients. 8,9 Inappropriate and prolonged use of PPIs in cirrhosis may lead to increased complications. Studies have shown that PPIs are associated with an increased incidence of serious complications such as spontaneous bacterial peritonitis (SBP) and hepatic encephalopathy (HE) in cirrhotic patients, [10][11][12] which may be due to an elevated pH value in the gastrointestinal tract that causes dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic liver disease has been constantly increasing worldwide, in particular in Western countries, and liver cirrhosis is the twelfth leading cause of death globally 5–7 . About 46%–78% of the patients with cirrhosis have been treated with acid suppression therapy, as it may be associated with a reduction in gastrointestinal rebleeding in cirrhotic patients 8,9 . Inappropriate and prolonged use of PPIs in cirrhosis may lead to increased complications.…”
Section: Introductionmentioning
confidence: 99%